Did America have a Christian founding?: separating modern myth from historical truth - Hall, Mark David (Nelson Books, 2019)
The myth of the founders' deism -- The United States does not have a godless constitution -- Thomas Jefferson, James Madison, and the first amendment -- The founders believed civic authorities should protect, promote, and encourage religion and morality -- Christianity, religious liberty, and religious exemptions.